Anatomy & Physiology Revealed : (MaGraw-Hill, 2006)
Experience interactive cadaver dissection... . Cadaver photos blended with a state-of-the-art layering technique let you peel away layers of the human body to reveal structures beneath the surface. This.... program includes animations, radiologic imaging, audio pronunciations, and a comprehensive quizzing tool.